Promoción y difusión de la biblioteca pública "La Delicia" del barrio Cotocollao, distrito metropolitano de Quito y su incidencia en los servicios de información a los usuarios. Periodo 2013-2014 - Molina Suárez, Maribel (2014)
This thesis entitled: PROMOTION AND DISSEMINATION OF PUBLIC LIBRARY "DELIGHT" DEL BARRIO COTOCOLLAO, METROPOLITAN DISTRICT OF QUITO AND ITS IMPACT ON INFORMATION SERVICES USERS. PERIOD 2013-2014. The general objective that guided the research was: To present a professional scientific and technical information, the importance of the promotion and dissemination of libraries, the user closer to the services of public libraries. The methods used for the preparation of this research work were: scientific, inductive, deductive, analytical, synthetic, descriptive statistic. Techniques used were: the survey of personnel associated with the library (4) and users (140) of "La Delicia" the neighborhood Cotocollao Library to establish information services that require consolidated through a series of questions designed torque effect. The most outstanding results are determined that 75% of users if they use the library due to the promotion and dissemination, while 25% of users do not; was determined that 39% of users require the implementation of photocopy for 34% of users should be implemented loan service delivery and 23% should improve internal loan service.